PENGARUH KERAGAMAN PRODUK DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN - Kanserina, Sesa Firty; Andayani, Sri; Mulyati, Diana Juni (Jurnal Dinamika Administrasi Bisnis, 2017)
In the conditions of competition in the field of culinary Yang Business The tighter the singer, then success Of Marketing activities Very determined by development of marketing strategies which are used. To review Culinary business won the hearts of competition, then the culinary business development strategy should be noticed that the right to buy consumer choose to review in the cafe only prayer was from consumer behavior problems. By therefore please note some factors  get involved hearts hearts behaviour consumer especially decision. By therefore hearts writers wanted singer research examined the influence of diversity products and store atmosphere against buying decision to review select places to eat the comfort for consumers entitled "Diversity influence Products And Buying Decision Against shop atmosphere in the cafe breechocolaterie".               Singer study aims to determine the effect of diversity Product review (X1) and the atmosphere of the store (X2) Buying Decision Against (Y). Research operates Singer is a quantitative method. population research singer is the buying consumer or breechocolaterie been at the cafe, the sample is a visitor who purchased or breechocolaterie been in the cafe for 96 orangutans.               The coefficient of determination (R) of 0.409, OR 40.9%. Value singer influenced by product diversity and store atmosphere Against Buying Decision. From the F test and T test showed that the diversity of products and the store atmosphere Good significant effect Operates Operates simultaneously or partial. Operates partial showed that the diversity of products has a dominant influence Against The Purchase Decision. Keywords: Diversity of products, store ambiance, Purchase Decision